Influência do treinamento aquático na resistência muscular, equilíbrio e marcha em idosas obesas: ensaio clínico randomizado - Giacovoni Neta, Amina Hamad (2019)
Introduction: Resistance aquatic training for lower limbs is indicated to potentiate maximal isometric strength of knee extensors and improve balance and mobility function in order to decrease the risk of falls in the obese elderly population. Objective: To investigate the effect of the water resistance training program on strength and muscular endurance, balance and gait in obese elderly. Methods: It is a randomized, two-arm, parallel, open-label trial with simple randomization. In the aquatic group (GA; n = 13), resistance training was performed and no intervention or treatment was performed in the control group (CG; n = 9). The volunteers were submitted to physical tests, anthropometric evaluations and analyzes of body composition and quality of life. The water resistance training program was carried out over a period of 11 weeks, twice weekly frequency and duration of 35 minutes each session. Results: There was an improvement in the performance of the sit and stand test of the chair from 12.31 ± 1.79 repetitions to 17.62 ± 3.09 repetitions, at equilibrium from 36.93 ± 2.56 points to 39.01 ± 0 , 00 points, gait from 14.9 ± 2.81 points to 17.6 ± 0.76 points and physical function from 3.7 (3.2-4.3) to 4.3 (3.9-4, 8) and increased flexibility from 12.82 ± 11.93 cm to 22.81 ± 9.77 cm in GA. Conclusion: The aquatic training program promoted increased strength and muscular endurance and flexibility, improved balance, gait and physical function in obese elderly women.